59 Prognosis of cervical cancer when diagnosed during pregnancy - Lydia M. Makepeace; Alexandra N. Spirtos; Anjali Nambiar; Aldeboran N. Rodriguez; Elaine Duryea; Catherine Y. Spong; Jayanthi Lea (Elsevier, 2023)
Objectives: Cervical cancer (CC) occurs in 0.1-12 per 10,000 pregnancies. Management of these patients is largely based on case reports and expert opinion. While data suggests that pregnancy does not adversely affect oncologic outcomes, timing and treatment modality are often impacted by pregnancy. In non-pregnant patients diagnosed with CC the mean reported recurrence rate is 5-10%. We report treatment patterns as well as obstetric and oncologic outcomes in patients undergoing treatment for CC in pregnancy. Methods: Following IRB approval, a retrospective review of all patients with cervical cancer during pregnancy who delivered at our institution between 2009 and 2023 was performed. Data on demographics, histology, stage, treatment, obstetric and oncologic outcomes were analyzed using descriptive statistics. Results: We identified 19 patients who met the inclusion criteria. Mean age at diagnosis was 30.6 years, mean parity was 2.2 (range 0-5). The majority (79%) identified as Hispanic, 10.5 % as black and 10.5% as non-Hispanic white. One patient was diagnosed prior to pregnancy, 10 (53%) were diagnosed prior to 20 weeks and 8 (42%) after 20 weeks gestation. Seventeen patients were diagnosed with stage I disease, one patient with stage II and one patient with stage III. Fourteen patients delivered viable infants at an average gestational age of 37w3d. Cancer was the most common indication for delivery (57%) and 43% delivered for OB indications. Sixteen of 19 patients were treated during pregnancy or at delivery, 5 were treated prior to EGA <22 weeks. 15/17 stage I CC patients were treated withradical hysterectomy, one was treated with LEEP in pregnancy and laparoscopic hysterectomy after delivery and one was treated with postpartum pelvic radiation. Patients with stage II and III CC were treated with chemoradiation. 15/19 patients are NED at median FU of 33 months. Four of 19 (21%) patients had disease recurrence. 18% (3/17) with stage I disease recurred. Two patients died of disease. Conclusions: Cervical cancer recurrence rates are significantly worse in patients with cancer during pregnancy, despite most patients presenting with stage I disease.